Designing Stable Deep‐Blue Thermally Activated Delayed Fluorescence Emitters through Controlling the Intrinsic Stability of Triplet Excitons. Issue 12 (18th March 2022) - Kang, Hosuk; Ihn, Soo‐Ghang; Kim, Inkoo; Chung, Yeon Sook; Jeon, Soon Ok; Sim, Myungsun; Kim, Joonghyuk; Lee, Hasup; Son, Youngmok; Son, Won‐Joon; Jang, Inkook; Kim, Dae Sin; et al.
Abstract: Thermally activated delayed fluorescence (TADF) has emerged as a promising and pragmatic light‐generation method for producing efficient organic light‐emitting diodes (OLEDs). However, the low operational stability associated with blue‐light TADF emitters is a major drawback and the excited‐state molecular degradation process remains poorly understood. Archetypal TADF emitters are comprised of cycloamine donor and aromatic acceptor moieties, with the corresponding C–N bond considered as the weakest link in the molecular structure. Understanding mechanism of the C–N dissociation in the excited state is, thus, crucial to the engineering of more stable OLEDs. Here, by using a carbazole donor and a triazine acceptor with various functional groups, it is shown that the position of the triplet exciton is the key to enhancing operational stability and, therefore, device lifetime. Interestingly, repositioning the triplet exciton away from the C–N bond causes the dissociation pathway to diverge from a smooth transition state to a more abrupt conical intersection with a higher energy barrier. We realize a 2.3‐fold increase in device lifetime without compromising traditional design factors, such as the singlet–triplet energy gap, with judicious introduction of functional groups to the acceptor. Abstract : The position of triplet exciton is key to enhancing operational stability of organic light‐emitting diode device. With judicious selection of the functional group within the acceptor moiety, the locus of triplet exciton can be repositioned away from the weak carbon–nitrogen bond, entailing higher dissociation barrier in the excited state and leading to a 2.3‐fold increase in device lifetime.